2015
DOI: 10.1109/tifs.2015.2390136
|View full text |Cite
|
Sign up to set email alerts
|

Physical Layer Network Security in the Full-Duplex Relay System

Abstract: This paper investigates the secrecy performance of full duplex relay networks. The resulting analysis shows that full duplex relay networks have better secrecy performance than half duplex relay networks, if the self-interference can be well suppressed. We also propose a full duplex jamming relay network, in which the relay node transmits jamming signals while receiving the data from the source. While the full duplex jamming scheme has the same data rate as the half duplex scheme, the secrecy performance can b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
188
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 276 publications
(188 citation statements)
references
References 31 publications
0
188
0
Order By: Relevance
“…In Ref. [20], SOPs (Secrecy Outage Probabilities) with FD and HD relay were analyzed, and a jamming scheme was proposed to further improve the secrecy performance. A similar method was considered in Ref.…”
Section: Journal Of Communications and Information Networkmentioning
confidence: 99%
“…In Ref. [20], SOPs (Secrecy Outage Probabilities) with FD and HD relay were analyzed, and a jamming scheme was proposed to further improve the secrecy performance. A similar method was considered in Ref.…”
Section: Journal Of Communications and Information Networkmentioning
confidence: 99%
“…This paper analyzes the system throughput based on (4). If the data are local, throughput for access and backhaul links are separately obtained, but the derivation is not shown in this paper due to the space constraint 3 .…”
Section: Dual Antennal Selection At Tsbsmentioning
confidence: 99%
“…If the data are local, throughput for access and backhaul links are separately obtained, but the derivation is not shown in this paper due to the space constraint 3 . The optimum transmission and receiving antennas at T SBS should be selected by maximizing (4). It is clear from (3) that γ B k depends on both receiving and transmission antennas.…”
Section: Dual Antennal Selection At Tsbsmentioning
confidence: 99%
“…For example, the IBFD can provide a better way to detect collisions in contention-based access protocols [8]. Also, in [9], it is reported that IBFD can improve the secrecy of relay networks significantly. In this study, we focus on the improvement of user data rate in a capacity-demanding indoor environment.…”
Section: Introductionmentioning
confidence: 99%